Health and Disease among Adolescent Urban School Girls in Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: Adolescence is an important phase of life and adolescent girls have specific health related problems. The aim of the study was to address the health-related issues of urban school going adolescent girls from a lower-middle income country.Materials and methods: A cross-sectional study was performed among 1315 school high-school girls. Demographic and socioeconomic parameters were recorded and health related behaviours and problems analysed.Results: Age ranged from 10 to 17 years. Immunization and deworming rates were 98.17% and 57.41%, respectively and deworming significantly reduced in higher classes (p=0.00). Major physical complaints were eye problems (583, 44.33%), allergy to various substances (500, 38.02%), headache (435, 33.08%) and menstrual problems (334, 25.40%). Obesity and overweight were significantly more in higher classes and underweight in lower classes (p